MORPHOLOGICAL CHARACTERIZATION OF ROOT INHABITING ENDOPHYTIC BACTERIA - RASHEED, R; MEHMOOD, MA; HAMEED, A; ANJUM, S; SHER, MA; AHMAD, S; FAROOQ, MA; ALAM, MW; BINYAMIN, R; ALI, S (Biological and Clinical Sciences Research Journal, 2023)
Endophytic bacteria (EBs) are beneficial to stimulating plant growth. However, little information about the EBs associated with soybean plant roots is available. This study examined the diversity of ten EBs isolated from soybean root tissues. Morphological and biochemical characterization methods revealed significant variation among the isolates. Most isolates displayed smooth colony surfaces, regular shapes, and rod-shaped cells. However, Bacterial Strain-5 and 10 exhibited rough surfaces and irregular shapes, while Bacterial Strain-4 displayed round cell shapes instead of the typical rod morphology. Moreover, the isolates demonstrated diverse pigmentation, with strains showing various shades of white, creamy, light yellow, pinkish red, Creamish, yellow, and red. In KOH test, three strains (2, 6, and 9) showed positive reactions to KOH, while the remaining seven strains (1, 3, 4, 5, 7, 8, and 10) showed negative reactions. The catalase test confirmed that four strains (1, 2, 6, and 9) were gram-negative, and the six strains (3, 4, 5, 7, 8 and 10) were gram-positive. In the gram staining test, seven strains (1, 2, 3, 6, 8, 9, and 10) were gram-negative, while the remaining three strains (4, 5, and 7) were gram-positive. Finally, in the starch hydrolysis test, seven strains (1, 2, 3, 6, 8, 9, and 10) were gram-negative, whereas the three strains (4, 5 and 7) were gram-positive. This study will help us identify various EBs that could play a role in the nodule formation and adaptation of soybean plants in diverse soil conditions in Pakistan.